Shark heart : a love story - Habeck, Emily (Marysue Rucci Books, 2023)
"For Lewis and Wren, their first year of marriage is also their last. A few weeks after their wedding, Lewis receives a rare diagnosis. He will retain most of his consciousness, memories, and intellect, but his physical body will gradually turn into a great white shark. As Lewis develops the features and impulses of one of the most predatory creatures in the ocean, his complicated artist's heart struggles to make peace with his unfulfilled dreams. At first, Wren internally resists her husband's fate. Is there a way for them to be together after Lewis changes? Then, a glimpse of Lewis's developing carnivorous nature activates long-repressed memories for Wren, whose story vacillates between her childhood living on a houseboat in Oklahoma, her time with a college ex-girlfriend, and her unusual friendship with a woman pregnant with twin birds. Woven throughout this bold novel is the story of Wren's mother, Angela, who becomes pregnant with Wren at fifteen in an abusive relationship amidst her parents' crumbling marriage. In the present, all of Wren's grief eventually collides, and she is forced to make an impossible choice"--